Teachers' information literacy levels in one cluster school in Malaysia/ Nurul Aini Othman, Raja Abdullah Yaacob, AP Azli Bunawan and Mohd Idzwan Salleh - Othman, Nurul Aini; Yaacob, Raja Abdullah; Bunawan, AP Azli; Salleh, Mohd Idzwan (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
Information literacy IL has become essential, especially in the field of education. The implementation the IL skills program in educational institutes is no longer the sole responsibilities of the school librarians but also shared by those involved in educating the students with special reference to the teachers. However, the success of the IL skill programs depends on the capability of the teachers which is also dependent on their IL levels. The main objective of the study is to investigate the level of IL skills among the teachers and their awareness of the importance of IL ski/ls. The IL skills of the teachers need to be identified in order to plan for the right approach to improve their IL skills. The levels of teachers' awareness on the importance of IL towards raising the academic excellence among teachers and students also need to be measured. Questionnaires were used as the tools to collect the data and supported with interviews. The results show that IL skills level of teachers in SMK Abdul Rahman Talib Kuantan are high and most of the teachers are aware of the importance of IL skills. However, the Ministry of Education should provide more formal IL programs for teachers to ensure that the transmission of IL skills in the classrooms are efficient and the challenges faced by the teachers can be surmounted.